Settlement of inheritance relations in bilateral international agreements of Ukraine with foreign states on legal assistance in civil cases - Karmaza , Oleksandra O.; Hrabovska, Oksana O.; Zakharova, Olena S. (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The main features of inheritance relations with a foreign element are given. The main issues to be resolved in inheritance relations with the help of international agreements concluded by Ukraine with foreign states on legal assistance in civil cases were identified. It has been established that the norms of two dozen bilateral international agreements on legal assistance and about three dozen consular conventions that Ukraine has concluded with many states are devoted to the issue of international inheritance. Some of the conventions operate in the order of succession of Ukraine after the collapse of the USSR. Comparative analysis of the content of the texts of bilateral international agreements of Ukraine with foreign states on legal assistance in civil matters allowed classifying them by methods of regulation of inheritance relations into three groups: ones that do not contain separate articles (articles) on the regulation of inheritance relations; agreements on legal relations and legal assistance in civil matters between Ukraine and foreign countries, which contain provisions on inheritance relations, which in turn are divided into two groups depending on the structure and content of the articles: inheritance cases and the right to inheritance. The analysis gives grounds to claim the lack of a unified approach to the conclusion of contracts in the third group. This cannot be explained by the will of the parties, because the content of this group of agreements has a high level of identity. The agreement between Ukraine and the Republic of Cyprus on legal assistance in civil matters, which has a separate section IV on inheritance, has an exceptional content in the regulation of inheritance relations, but in comparison with other two groups of agreements with foreign countries contains very brief information. From the analyzed bilateral international agreements it was concluded that most aspects of inheritance relations are regulated by the personal law of a testator or the right of location of a property. There is a gradual overcoming of the problem of splitting the inheritance status, regardless of the location of the inheritance, the spread of the possibility of choosing the applicable law to the estate.